The Effect of Compound Exercises on the Effectiveness of Offensive Tactical Performance of Youth Football Players - Jaafar AbdAbu Al-Thar Abd, (Musamus Journal of Physical Education and Sport (MJPES), 2025)
The significance of this study emerged from the use of compound exercises (technical-tactical) aimed at developing the effectiveness of offensive tactical performance of attacking players in the final third of the football field. Additionally, these exercises help improve the overall capabilities of players during competition and enable them to make correct decisions during tactical performance, which enhances teamwork and cohesion when the attack is collective. The study aimed to design compound exercises for youth football players and to examine their impact on the effectiveness of offensive tactical performance.The researcher hypothesized that compound exercises have a positive effect on the offensive tactical performance of the experimental group, as evidenced by the comparison between pre-test and post-test results. The compound exercises significantly improved the post-test performance of the experimental group compared to the control group in terms of offensive tactical effectiveness.The research methodology followed an experimental design, utilizing both experimental and control groups to suit the research problem and achieve its objectives. The study population consisted of youth players from clubs in the center of Wasit Governorate participating in the provincial league for the 2023–2024 season, totaling 167 players across 8 clubs (as shown in Table 3). The research sample was purposively selected, consisting solely of attacking players: Wasit Club as the experimental group with 8 players, and Al-Shohada Club as the control group with 8 players.After conducting the pre-test, applying the compound exercises, and performing the post-test, the data were analyzed statistically using the SPSS statistical package. Following the discussion of the results, the researcher concluded that the designed compound exercises produced positive outcomes in offensive tactical performance due to their high similarity to competitive football matches. The integration of all football skills—including passing, shooting, dribbling, receiving, rolling, and the interconnection of these skills—contributed to enhancing the effectiveness of offensive tactical performance in the experimental group.